Plasmavigilance—Adverse events among US Source plasma donors. Issue 10 (14th August 2021) - Schreiber, George B.; Becker, Mark; Fransen, Michelle; Hershman, Janet; Lenart, James; Song, Guang; Simon, Toby
Abstract: Background: Source plasma (SP) is the primary starting material for 87% of plasma‐derived medicinal products globally. Plasmavigilance is a program designed to collect, analyze, and monitor donor adverse events (AEs) across the SP collection industry. Donor retention depends on donors having a safe and satisfactory experience. This study analyzes AE rates and SP donor characteristics that may be predictors of an AE. Study Design and Methods: Donation data for 1.1 million donors making 12, 183, 182 SP donations over a 4‐month period were analyzed. This represented approximately 72% of the donations collected by the U.S. plasma industry. The Standard for Recording Donor Adverse Events was used for AE definitions and classifications. Results: The overall AE rate was 15.85/10 4 donations. The two AEs with the highest rates were Hypotensive and Phlebotomy events (8.32 and 5.91/10 4 donations, respectively). Females had higher overall AE rates than males (25.76 vs. 9.85/10 4 donations), and first‐time donors had higher overall AE rates than repeat donors (136.66 vs. 12.37/10 4 donations). Weight, body mass index, age, and pre‐donation estimated blood volume also were predictors of AE. Discussion: SP donors have low AE rates with 90% being events classified as Hypotensive or Phlebotomy. Special attention and mitigation strategies should be directed to donors who are young, lightweight (between 100 and 124 pounds), female, or first‐time donors to further reduce the incidence of AE, continue to ensure the donor has a safe experience, and facilitate donor retention. Abstract : See editorial on page 2803–2805, in this issue